Kinetic Modelling of the Photocatalytic Inactivation of Bacteria - Marugan, J. (2010)
This work analyzes the kinetic modelling of the photocatalytic inactivation of E. coli in water using different types of kinetic models; from an empirical equation to an intrinsic kinetic model including explicit radiation absorption effects. Simple empirical equations lead to lower fitting errors, but require a total of 12 parameters to reproduce the results of four inactivation curves when the catalyst concentration was increased. Moreover, these parameters have no physical meaning and cannot be extrapolated to different experimental conditions. The use of a pseudomechanistic model based on a simplified reaction mechanism reduces the number of required kinetic parameters to 6, being the kinetic constant the only parameter that depends on the catalyst concentration. Finally, a simple modification of a kinetic model based on the intrinsic mechanism of photocatalytic reactions including explicit radiation absorption effects achieved the fitting of all the experiments with only three parameters. The main advantage of this approach is that the kinetic parameters estimated for the model become independent of the irradiation form, as well as the reactor size and its geometrical configuration, providing the necessary information for scaling-up and design of commercial-scale photoreactors for water disinfection.